Evaluasi Pelaksanaan Flexible Pavement Menggunakan Aspal Buton. - Hadi, Yohanes Martono (UNIVERSITAS LAMPUNG, 2010)
This research takes the samples in two locations of hardened-layer implementation using asbuton as the substitution of visco elastic. The research is conducted at the road paths of national street, Jambi Province. Data are gathered through several surveys: pre-conducting survey, on conducting survey, and post-conducting survey, within a year. This research aims to compare the result of two locations and the result of Job Mix Formula which are correlated to both laboratory test result of asbuton producer and laboratory test result of Engineering Faculty of Lampung University. The result of laboratory data analysis and material used test show the causes of failure on one of the road paths though the result of laboratory test and field test remain the same. Asbuton has similar characteristics to visco elastic. The influence of temperature, specifically mixing temperature and compact temperature, is very dominant toward end result of pavement product. Mixing temperature is determined by AMP capability to produce high-heat (+/- 1700C) in aggregate drying process within â€œdrying-drumâ€. Meanwhile AMP with diesel fuel is not capable to produce such high-heat, except if AMP employs coal. Besides, travel time from AMP to exposure location will very much influence the pavement quality. The research findings show the comparison between the conducting of laboratory test and the result of post-conducting at two locations in 2009. The conclusion drawn from the field test are: mixing temperature is very dominant to determine the end result and there is a problem as the result of asbuton substitution with visco elastic.